Professional Socialization among Nursing Students - Sruthi M; Aleena Baiju; Swathi Krishna T P (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective : The objectives of our study is to determine the professional socialization among nursing students,to find out the association between professional socialization and demographic characteristics and to findthe subgroup comparison of level of professional socialization among outgoing batch students and first yearB.Sc. nursing studentsMethodology: A descriptive study was conducted among all four years of nursing students of a privatenursing college. Nursing students who meet the inclusion criteria (357) were selected using purposivesampling.Results: The majority of the students are ‘Experts’ in maintaining professional socialization. But in thesubgroup comparison of level of Professional socialization among the final year students with first yearshowed a 1.1% less in ‘Expert’ category. The results showed a significant association of level of professionalsocialization with ‘Gender’, ‘Mode of Admission’ and ‘Reason for selecting nursing as a profession’Conclusion: The need for developing professional socialization has to be considered at the most priority.The results of this study shows the need for introducing new plans to make sure that the students level ofsocialization